Effect of N and K Fertilizers on Growth, Yield and Quality of Pear (Pyrus pyrifolia) - PP S Gill (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2017)
The effect of different combined doses of N and K fertilizers on plant growth, fruit quality and foliar elemental composition of pear cv. Patharnakh was investigated. Experimental plants were supplied with different levels of N (460, 690 and 920 g N /plant) and K (600, 900, 1200 and 1500 g K2O/plant) in the form of Urea and Muriate of Potash (MOP) fertilizers. From the results, it was found that nitrogen application increased number of fruits/plant, trunk cross-sectional area (TCSA), shoot length and leaf N content, whereas, K application improved fruit firmness, total soluble solids (TSS), and leaf K content. Fruits harvested from T4 (460 g N:1500 g K2O /plant) treatment recorded maximum firmness. Plants under T9 (920 g N: 600 g K2O /plant) treatment showed the maximum increase in shoot length, and TCSA, whereas, T6 (690 g N : 900 g K2O /plant) resulted in maximum fruit yield. Leaf N and K concentrations improved with applications of the respective fertilizer.